The Estradiol Synthesis Inhibitor Formestane Diminishes the Ability of Sevoflurane to Induce Neurodevelopmental Abnormalities in Male Rats - Wang, Jie; Yang, Baofeng; Ju, Lingsha; Yang, Jiaojiao; Allen, Andrea; Zhang, Jiaqiang; Martynyuk, Anatoly E. (Frontiers in Systems Neuroscience, 2020)
Background: Children exposed to general anesthesia early in life may develop significant neurodevelopmental abnormalities. Establishing safer pediatric anesthesia is impeded by a lack of understanding of the initial mediating mechanisms of such effects. Here, we tested the roles of the sex steroid 17β-estradiol (E2) and excitatory GABA type A receptor signaling, whose specific developmental effects in rodents occur during the age period of increased vulnerability to the developmental effects of general anesthetics. Methods: Sprague-Dawley rats were pretreated with the inhibitors of E2 synthesis, formestane, or the Na+-K+-2Cl- (NKCC1) Cl- importer, bumetanide, prior to anesthesia with 2.1% sevoflurane for 6 h on postnatal (P) day 4, P5, or P6. The subsequent exposure to sevoflurane-induced electroencephalography-detectable seizures (P~10), behavior during the elevated plus maze (EPM, P~60) and prepulse inhibition of acoustic startle (PPI, P~70) tests, and corticosterone responses to stress (P~80) were studied. Results: Sevoflurane induced increased susceptibility to repeated exposure to sevoflurane-caused electroencephalography-detectable seizures (F(3,24) = 7.445, P = 0.001) and behavioral deficiencies in male rats during the EPM (F(3,55) = 4.397, P = 0.008) and PPI (F(3,110) = 5.222, P = 0.003) tests. The corticosterone responses to stress were increased in males (F(3,16) = 11.906, P < 0.001) and females (F(3,20) = 11.010, P < 0.001). Formestane and bumetanide prevented these effects of sevoflurane. Conclusion: These results, along with previously published data, suggest that sevoflurane-enhanced E2 synthesis and excitatory GABAAR signaling, which may be further positively modulated by E2, represent initial steps in the developmental effects of the anesthetic.